Web-Based Academic Information and Monitoring System at Kudus State Madrasah Ibtidaiyah - Putri, Sevara Humaira; Rhoedy Setiawan; Yudie Irawan (Universitas Budi Darma, 2025)
This research is based on the needs of Madrasah Ibtidaiyah Negeri Kudus to improve communication and academic management in the digital age. The main issues raised are suboptimal grade recording systems, absenteeism, and the rapid and structured dissemination of important information. The objective of this research is to create and develop a web-based academic information system that can be monitored via WhatsApp. This system will enable teachers, parents, and school administrators to easily access information. The Waterfall software development model, which consists of the stages of needs analysis, design, implementation, testing, and maintenance, is the methodology used in this research. Data was collected through interviews and direct observation of academic activities on the school campus. This system enables the recording of student grades and attendance data on a daily basis. It also allows parents to receive automatic notifications about learning activities, class schedules, and other important information. This research resulted in a web-based application that has the ability to improve academic recording and reporting, enhance communication between schools and parents, and support real-time transparency of academic information. By using this system, the State Elementary School in Kudus is expected to be better prepared to face the digital transformation occurring in the world of education.